2015
DOI: 10.1186/s40360-015-0028-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, trends, patterns and associations of analgesic use in Germany

Abstract: BackgroundDespite the public health relevance of analgesic use, large-scale studies on this topic in Germany are lacking. This study describes the prevalence, trends, associations and patterns of use of prescription and over-the-counter (OTC) analgesics, focusing on five of the most common agents: aspirin, diclofenac, ibuprofen, naproxen and paracetamol.MethodsData from two representative population-based surveys: The German National Health Interview and Examination Survey 1998 (GNHIES98 n = 7099) and the Germ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
83
3
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(113 citation statements)
references
References 44 publications
19
83
3
8
Order By: Relevance
“…[14,16] there is another study in Germany shown the opposite result. [17] Most of the analgesics user in this study are taking one tablet mostly for minor pains such as fever and headache which shows lack of information about appropriate adult dose which agrees with a Norwegian study which says that their respondents were using a lower dose of OTC drugs and had not exceeded the maximum dose. [18,19] We also encountered most participates who were convinced that NSAIDs and paracetamol have no side effects.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[14,16] there is another study in Germany shown the opposite result. [17] Most of the analgesics user in this study are taking one tablet mostly for minor pains such as fever and headache which shows lack of information about appropriate adult dose which agrees with a Norwegian study which says that their respondents were using a lower dose of OTC drugs and had not exceeded the maximum dose. [18,19] We also encountered most participates who were convinced that NSAIDs and paracetamol have no side effects.…”
Section: Discussionsupporting
confidence: 62%
“…[10,20,21] Our findings generally revealed no significant difference in use of analgesics between male and female as the previous study in Iran and that converse to other studies in Riyadh, Taif, turkey, Germany, and Norway. [1,14,15,17,22,23] Like our findings in Saudi, many studies have also shown there is a significant age difference in the prevalence of analgesic use among the population. Studies conducted in Taif, Sweden, United States, and Norway have shown an association between age and analgesic use.…”
Section: Discussionsupporting
confidence: 45%
“…The higher use of OTC NSAIDs in female and younger patients has been reported in previous studies (Duong et al, 2014;Sarganas et al, 2015). It was also found Ibuprofen was the most commonly purchased NSAIDs and this fact was similar to the results of other studies in Germany, France and the United States (Duong et al, 2014;Sarganas et al, 2015;Wilcox et al, 2005). In the present study, the education level of most of OTC NSAIDs purchasers were more than diploma, and, among all the participants, the doctorate clients had more information about NSAIDs.…”
Section: Discussionsupporting
confidence: 81%
“…NSAIDs usage is associated with gastrointestinal problems, kidney damages, asthma worsening in affected patients, increasing risk of post-surgery and post-partum bleeding, erectile dysfunction, and complications regarding conception and pregnancy (Sharma et al, 2015). Important drug interactions occur when these medications are used with several drugs such as selective serotonin reuptake inhibitors (SSRIs), anticoagulants, antiplatelet drugs (Goldstein and Cryer, 2015) and antihypertensive drugs (Floor-Schreudering et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation